The Effect of the Usage of Computer-Based Assistive Devices on the Functioning and Quality of Life of Individuals who are Blind or have low Vision. (January 2018) - Rosner, Yotam; Perlman, Amotz
Introduction: The Israel Ministry of Social Affairs and Social Services subsidizes computer-based assistive devices for individuals with visual impairments (that is, those who are blind or have low vision) to assist these individuals in their interactions with computers and thus to enhance their independence and quality of life. The aim of this study was to examine the effect of computer usage on the quality of life of computer-based assistive device users, and to evaluate their capacity to carry out computer-based tasks. Methods: The study was conducted between the years 2013 and 2015. Questionnaires were provided to 96 randomly sampled individuals with visual impairments. These questionnaires were designed to collect information about the quality of life, types and frequency of computer use, satisfaction with the assistive devices, and the effects of computer-based assistive device usage on the participants' lives. In addition, the study evaluated participants' performance in tasks such as e-mail use, Internet surfing, and the use of Microsoft Word; participants performed these tasks on their personal computers. The research sample accounts for about 10% of visually impaired persons in Israel. Results: Findings suggest that participants use computer-based assistive devices frequently (four hours a day on average), primarily for leisure (three hours on average). Participants also report high satisfaction with their devices (mean of 3.98 out of the maximum score of 5.00) and indicate that the devices have improved their quality of life (mean 3.67 out of 5.00) and leisure activities (mean 3.68 out of 5.00). Participants display high levels of task performance, especially in the use of Microsoft Word software (mean of 3.47 out of 5.00), and e-mail usage (mean of 3.81 out of 5.00). Discussion: The findings suggest that most participants use computer-based assistive devices daily and report a positive influence from them on their quality of life and activity. Implications for practitioners: The study suggests that welfare services and assistance organizations would benefit from subsidizing computer assistive devices for individuals with visual impairments.